2013
DOI: 10.1515/iral-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Language choices in L2 English sentence production: Why speakers could have used modal perfect but didn’t

Abstract: This study compared production of modal perfect sentences by native English speakers and advanced non-native English speakers from Asian L1 backgrounds in discourse and discourse-free contexts. In experiment 1, native and non-native speakers reconstructed modal perfect sentences from sentential anagrams under time pressure. Both speaker groups were faster to construct modal perfect sentences than closely matched control sentences. In experiment 2, native and non-native speakers read and responded orally to sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, this task may be difficult for learners, particularly non-native speakers of English, to connect, retrieve, and apply the acquired knowledge to the actual communicative usage of the past counterfactuality. One aspect in using counterfactuals is for criticism (Conroy & Cupples, 2013). Speakers of English in collectivism cultures tend to have less propensity to criticize others than their individualist counterparts (Conroy & Cupples, 2013; Hofstede et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this task may be difficult for learners, particularly non-native speakers of English, to connect, retrieve, and apply the acquired knowledge to the actual communicative usage of the past counterfactuality. One aspect in using counterfactuals is for criticism (Conroy & Cupples, 2013). Speakers of English in collectivism cultures tend to have less propensity to criticize others than their individualist counterparts (Conroy & Cupples, 2013; Hofstede et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One aspect in using counterfactuals is for criticism (Conroy & Cupples, 2013). Speakers of English in collectivism cultures tend to have less propensity to criticize others than their individualist counterparts (Conroy & Cupples, 2013; Hofstede et al, 2017). The use of focused communication tasks, such as impromptu speaking or storytelling, may be alternatively considered for future research as they may be more effective in capturing learners’ productive process of the English past counterfactuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu (2018) found that English L2 proficiency may correlate with speed of processing of counterfactual sentences in Chinese L1 . There is also indirect evidence that counterfactuality may be difficult to Chinese native speakers, as they have well-documented difficulty in learning and using English L2 counterfactuals (Chou, 2000; Conroy & Linda, 2013). In spite of the lack of interest among researchers, Bloom’s work is still cited (and refuted) in discussions of linguistic relativity research, whether in dedicated monographs (Deutscher, 2010; Everett, 2013) or in cognitive psychology textbooks (Friedenberg & Silverman, 2011; Galotti, 2017).…”
Section: Introductionmentioning
confidence: 99%